Corticotropin-releasing hormone modulates airway vagal preganglionic neurons of Sprague–Dawley rats at multiple synaptic sites via activation of its type 1 receptors: Implications for stress-associated airway vagal excitation. (4th July 2017) - Guo, Yuhong; Yan, Xianxia; Chen, Xingxin; He, Ding; Zeng, Ming; Chen, Yonghua; Xia, Chunmei; Qiu, Dongying; Wang, Jijiang
Highlights: Corticotropin-releasing hormone depolarized airway vagal preganglionic neuron (AVPN). Corticotropin-releasing hormone caused a tonic excitatory current in AVPN. Corticotropin-releasing hormone enhanced the glutamatergic synaptic inputs of AVPN. Corticotropin-releasing hormone enhanced the GABAergic synaptic inputs of AVPN. Type 1 receptor antagonist blocked the effects of corticotropin-releasing hormone. Abstract: Corticotropin-releasing hormone release is the final common pathway of stress-associated neuroendocrine responses. This study tested how corticotropin-releasing hormone modulates airway vagal preganglionic neurons. Airway vagal preganglionic neurons in neonatal rats were retrogradely labeled with fluorescent dye and identified in medullary slices, and their responses to corticotropin-releasing hormone (200 nmol L −1 ) were examined using whole-cell patch clamp. The results show that under current clamp, corticotropin-releasing hormone (200 nmol L −1 ) depolarized airway vagal preganglionic neurons and significantly increased the rate of their spontaneous firing. Under voltage clamp, corticotropin-releasing hormone caused a tonic inward current and significantly facilitated the spontaneous glutamatergic and GABAergic inputs of these neurons. Corticotropin-releasing hormone had no impact on the spontaneous glycinergic inputs of these neurons. In the preexistence of tetrodotoxin (1 μmol L −1 ), corticotropin-releasing hormone had no impact on the miniature excitatory or inhibitory postsynaptic currents, but still induced a tonic inward current and significantly increased the input resistance. The responses induced by corticotropin-releasing hormone were prevented by Antalarmin hydrochloride (50 μmol L −1 ), an antagonist of type 1 corticotropin-releasing hormone receptors, but insensitive to Astressin 2B (200 nmol L −1 ), an antagonist of type 2 corticotropin-releasing hormone receptors. These results suggest that corticotropin-releasing hormone excites airway vagal preganglionic neurons via activation of its type 1 receptors at multiple sites, which includes a direct postsynaptic excitatory action and presynaptic facilitation of both glutamatergic and GABAergic inputs. In stress, corticotropin-releasing hormone might be able to activate the airway vagal nerves and, consequently, participate in induction or exacerbation of airway disorders.